Liver Injury in Critically Ill and Non-critically Ill COVID-19 Patients: A Multicenter, Retrospective, Observational Study - Jiang, Saiping; Wang, Rongrong; Li, Lu; Hong, Dongsheng; Ru, Renping; Rao, Yuefeng; Miao, Jing; Chen, Na; Wu, Xiuhua; Ye, Ziqi; Hu, Yunzhen; Xie, Minghua; et al. (Frontiers in Medicine, 2020)
Background: Liver injury commonly occurs in patients with COVID-19. Limited data describe the occurrence regularity of liver injury in patients with different disease severity, and the causes and risk factors are unknown. We aim to investigate the incidence, characteristics, risk factors, and clinical outcomes of liver injury in patients with COVID-19. Methods: This retrospective observational study was conducted in three hospitals (Zhejiang, China). From 19 January 2020 to 20 February 2020, patients confirmed with COVID-19 (≥18 years) and without liver injury were enrolled and divided into non-critically and critically ill groups. The incidence and the characteristics of liver injury were compared between the two groups. Demographics, clinical characteristics, treatments, and treatment outcomes between patients with or without liver injury were compared within each group. The multivariable logistic regression model was used to explore the risk factors of liver injury. Results: The mean age of 131 enrolled patients was 51.2 years (standard deviation [SD]=16.1 years), and 70 (53.4%) patients were male. A total of 76 patients developed liver injury (mild 40.5%; moderate 15.3%; severe 2.3%) with median occurrence time of 10.0 days. Critically ill patients had higher and earlier occurrence (81.5% vs. 51.9%, 12.0 vs. 5.0 days; p<0.001), greater injury severity (p<0.001), and slower recovery (50.0% vs. 61.1%) of liver injury than non-critically ill patients. Multivariable regression showed that the number of concomitant medications (odds ratio [OR]=1.12, 95% confidence interval [CI]=1.05–1.21) and the combination treatment of lopinavir/ritonavir and arbidol (OR=3.58, 95% CI=1.44–9.52) were risk factors of liver injury in non-critically ill patients. The metabolism of arbidol can be significantly inhibited by lopinavir/ritonavir in vitro (p<0.005), which may be the underlying cause of drug-related liver injury. Liver injury was related to increased length of hospital stay (mean difference [MD]=3.2, 95% CI=1.3–5.2) and viral shedding time (MD: 3.0, 95% CI=1.0–4.9). Conclusions: Critically ill patients with COVID-19 suffered earlier occurrence, greater injury severity, and slower recovery from liver injury than non-critically ill patients. Drug factors were related to liver injury in non-critically ill patients. Liver injury was related to prolonged hospital stay and viral shedding time in patients with COVID-19.